Roman-Punktir. Indirektes Erzaehlen durch Leerstellen in Jurij Trifonovs Roman "Zeit und Ort" - Scheffler, Leonore (Vortraege und Abhandlungen zur Slavistik, 1998)
Jurij Trifonov's last great novel "Vremja i mesta", understood by the author to be his most important work, outlines in the experience of epic figures a contemporary historical period: Moscow, in the period from August 1937 to early 1980. Trifonov saw it as the most important task of literature as well as his personally most important task as a writer, "to represent the phenomenon of life and the phenomenon of time".